Advancing Research on Traditional Whole Systems Medicine Approaches - Paul J. Mills PhD; Sheila Patel MD; Tiffany Barsotti MTh; Christine Tara Peterson PhD; Deepak Chopra MD (SAGE Publishing, 2017)
While the intention of Integrative Medicine (IM) is whole person medicine, it has for the most part remained driven by individual modalities. Like the practice of IM itself, IM research too has been driven primarily by studies on individual modalities. There are significant challenges to moving research on whole systems medicine forward, with funding being at the top of the list. Historically, NIH has not been receptive to supporting research on whole systems, preferring instead to support studies that are more individual modality driven so that mechanisms can be identified. Purely mechanistic research, however, assumes unidirectional causality and linear responses yet clinical responses to whole systems approaches are more often multidirectional and dynamically unpredictable. The concept of emergence is applicable here. Whole systems approaches suggest that by incorporating therapies into holistic treatment programs we not only treat symptoms but accomplish more by activating the body's inherent self-organizing healing mechanisms and treat the root cause of illnesses as well as associated symptoms. Given that interest in integrative therapies with the general public and medical community is steadily increasing, there is need for more research that explores intact whole systems approaches to elucidate the relevant system-wide effects and dynamic interactions related to these practices.